Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas V Di SDN Antasan Besar 1 Dengan Menggukan Kombinasi Model Problem Based Learning (PBL) Talking Stick Dan Example Non Example - Septiana, Yuyun; Suhaimi (CV. ITTC INDONESIA, 2023)
The problem in this research is the low activity of students in grade 5 SDN Antasan Besar 1 Banjarmasin. This problem causes learning to be teacher-centered, students are not directly involved in the learning process, and teachers still use conventional learning models. To achieve the goal of increasing student activity and learning outcomes, this study used a combination of Problem Based Learning, Talking Stick, and Example Non Example models to improve the learning process in grade 5 students at SDN Antasan Besar 1 Banjarmasin, totaling 32 students, involved in this research during the second semester of the 2022/2023 academic year. Qualitative and quantitative data are used in this study. The results showed that teacher activity and student activity at each cycle meeting were in accordance with the plan, with a score increasing from 24 to 32 with the